Novel ELISA Based on Purified and Recombinant Antigens from Toxocara Canis Exhibits a High Diagnostic Sensitivity. (March 2022) - Schaefer, J.; Menge, B.; Stiba, K.; Dibbern, J.; Borchardt-Lohölter, V.; Steinhagen, K.; Schlumberger, W.
Abstract : Purpose: Toxocariasis is a zoonosis that is mainly caused by the dog roundworm Toxocara canis and the cat roundworm T. cati . The prevalence of T. canis -specific antibodies in humans is 2-5% in Germany. Many infections with Toxocara spp. have a subclinical course, but can develop into a severe disease, with visceral, ocular, or neurotoxic manifestations. While first serological antibody detection methods were based on the whole lysate from T. canis larvae, meanwhile Toxocara excretory/secretory (TES) antigens from larvae cultures are used. Here, we evaluated the diagnostic performance of a new ELISA based on a highly purified larval antigen from T. canis and recombinant TES antigen. Methods & Materials: [1] Comparison with an external quality assessment scheme (NEQAS, UK) encompassing 9 positive and 8 negative sera. [2] Agreement study with a commercial Toxocara canis IgG ELISA (based on T. canis antigens; IBL International, Germany) including 117 sera pre-characterised by IBL ELISA. [3] Specificity was evaluated with respect to a control panel containing 586 sera from healthy blood donors, 98 from pregnant women and 197 from children as well as a cross-reactivity panel (135 sera from patients infected with Strongyloides, Schistosoma, Ascaris, Trichinella and other parasitic/bacterial infections). Results: Results obtained with the Anti-Toxocara ELISA were 100% in agreement with the NEQAS target values (sensitivity: 88.9%, specificity: 100%). The agreement between the two methods was substantial (79%, κ=0.57). The EUROIMMUN ELISA found 86 and the IBL ELISA 71 positive samples (negative predictive value=1). The EUROIMMUN ELISA found 23 and the IBL ELISA 41 negative samples. Thirteen discrepant samples were positive in the EUROIMMUN ELISA but negative in the IBL ELISA. The Anti-Toxocara ELISA was reactive in 25.9% of samples in the cross-reactivity panel and in 4.5% of the samples from healthy individuals, yielding a combined specificity of 92.6%. Conclusion: The novel Anti-Toxocara ELISA is a valuable screening test for sensitive serological detection of T. canis infections. Possible past infections or double infections with other parasites should be considered when evaluating the test result. A positive ELISA test result could be confirmed by a corresponding Western blot, which is available from EUROIMMUN.